Proteomic analysis of stachyose contribution to the growth of Lactobacillus acidophilus CICC22162. Issue 5 (16th May 2018) - Zhong, Xian-feng; Zhang, Yu-bo; Huang, Gui-dong; Ouyang, Yong-zhong; Liao, Dong-jiang; Peng, Jia-wei; Huang, Wei-zhi
Abstract : Stachyose is a functional oligosaccharide, acting as a potential prebiotic for colonic fermentation. Abstract : Stachyose is a functional oligosaccharide, acting as a potential prebiotic for colonic fermentation. To understand the mechanism of how stachyose promotes the growth of probiotic bacterium, we analyzed the differences of the proteome of Lactobacillus acidophilus grown on stachyose or glucose. By a combination of two-dimensional electrophoresis and mass spectrometry analysis, we observed 16 proteins differentially abundant under these two conditions and identified 9 protein spots. Six of these proteins were highly abundant when stachyose was used as the sole carbon source. They included the phosphotransferase system, the energy coupling factor (ECF) transporter and the mannose-6-phosphate isomerase, involved in the uptake and catabolism of stachyose in Lactobacillus acidophilus CICC22162. Supportively, these observations were validated by quantitative RT-PCR analysis and enzymatic activity determination. Positive correlation was found between the content of the proteins and their mRNA levels. Additionally, we explored the recognition mechanism for stachyose binding to the newly identified ECF transporter by MD simulations and free energy analysis. Taken together, these results provide new insights into the mechanism of stachyose in promoting the growth of probiotic bacterium.